Integration of Flexible Keypad Into Clothing (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The aim of this paper is to consider data input methods and technologies related to information input into electronic systems that would be suitable for smart garments. An overview of recent developments in the area of flexible switches is provided, describing processes used to fabricate these connections and highlighting issues and problems associated with it. Available soft button / keypad products are considered and keypad construction methods are analyzed. This study resulted in the creation of a flexible textile keypad prototype with row-and-column addressable structure and with breaking point technology underneath button design.